Biochemical Foundations of Indian Commerce Navigating the Intersection of Biology, Chemistry, and Economics - Dr.B.Elia; Dr.K.Lakshmana Rao; G Praveen Chakravarthi; Dr D S V N M Ramamurty; Vankudavathu Mallikarjuna Naik; Dr. Soamrouthu V.G.V.A.Prasad (The Bioscan, 2024)
In developing nations like India, this episteme across biology, chemistry, economics & commerce are crucial for our economic growth, innovation and global competitiveness. The review unveils the biochemical backbone of Indian commerce and its evolution into a mature revenue-generating tool over the years in terms of the interdependence of biochemistry, chemical processes, and economic development in core competency sectors like pharmaceuticals, biotechnology, agriculture, and clean energy. The study explains that, in particular, biological and chemical innovations are critical in advancing bio-based industries and productivity and in shaping India’s economy into an export-oriented one. It underlying the importance of interdisciplinary approaches to economizing these industries and examples of biochemistry and commerce that were successfully integrated. This paper also examines policy frameworks in support of commercialization of biotechnologies and chemical innovations, as well as future trends and challenges in these sectors. This review serves as a guide for the way forward for economic growth in the country, by highlighting the biochemical basis of diverse fields that are on the rise in India.